Blind Channel Estimation Using Wavelet Denoising of Independent Component Analysis for LTE - Gamal Mabrouk Abdel-Hamid; Reham S. Saad (Institute of Advanced Engineering and Science, 2016)
A new proposal of blind channel estimation method for long term evoluation (LTE) based on combining advantages of denoising property of wavelet transform (WT) with blind estimation capability of independent component analysis (ICA) called wavelet denoising of ICA (WD-ICA) was presented. This new method increased the spectral efficiency compared to training based methods, and provided considerable performance enhancement over conventional ICA methods. The conventional blind channel estimation methods based on ICA were performed individually for each orthogonal frequency division multiplexing (OFDM) subcarrier. To reduce complexity of implementation of WD-ICA method, channel interpolation was used. This method was presented for multiple-input-multiple-output (MIMO) downlink LTE system. WD-ICA method was compared to conventional ICA methods and the Performance was evaluated by calculating normalized mean square error (NMSE) and bit error rate (BER). WD-ICA method as compared to the other known ICA channel estimation methods has lower complexity, lower value of NMSE, and lower value of BER, which indicates the superiority of the proposed method.